DAMPAK PENGUMUMAN MERGER TERHADAP ABNORMAL RETURN DAN AKTIVITAS VOLUME PERDAGANGAN SAHAM (STUDI PERBANKAN DI BEI) - Hj. Chaerunnisa Rumianti (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
One event that is about to test the strength of the charge information is event merger announcement in companies engaged in banking sector. Event day chosen was dated July 6, 2009 and August 2, 2010. The issue is considered attractive because of alleged contradictions between the advantages that can be gained from the merger and the fact that there is the banking business environment when it has a condition that is not too good . The purpose of this study in addition to knowing the price reaction and the activity of trading volume (trading volume activity) shares in the Jakarta Stock Exchange on the merger announcement event, also to determine whether there are differences in average abnormal return (average abnormal return) and trading volume activity between before and after the merger announcement. Samples selected stocks in this study are stocks that are included in the banking sector and the LQ - 45 with the consideration that these stocks are stock that can represent the population of the banking sector from the perspective of the number of shares traded and market capitalization value. To examine the information content (information content) of the event, use the event study method. The test results indicate that the Jakarta Stock Exchange does not react to the events of the merger announcement . This is evident from the absence of test results that provide a level of significance is set at a minimum of 95 % . The difference in the average abnormal return at the time of the announcement and about the announcement was also not proven significantly. Meanwhile, the difference in average trading volume activity at the time of the announcement and about the announcement actually showed the opposite, which is shown to be significant at the 99% confidence level .